Does Learning Interest Mediate Computer Self-Efficacy and Internet Use on Learning Achievement? (Accounting Class student overview) - Alifrum Shaleha Dewi Rahmah; Mardi Mardi; Achmad Fauzi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Learning achievement is an achievement that has been achieved by students during the learning process according to the target time which is manifested in the form of numbers, letters, symbols and certain sentences as a standard of student completeness in learning. Achievement of learning achievement among students can vary because of many factors that influence it. For example, internal factors in the form of computer self-efficacy and internet use and external factors in the form of interest in learning. This study aims to determine whether interest in learning is able to mediate computer self-efficacy and internet use on learning achievement. By using a quantitative approach, the sample was chosen randomly (proportionate stratified random sampling) obtained 108 students of Class XI Accounting. Data were collected using an online questionnaire (on a Likert scale). Data were analyzed using descriptive statistics, hypotheses were analyzed multiple regression, and path analysis and single test (for indirect effects). The test results conclude that interest in learning can mediate computer self-efficacy and the use of the internet on learning achievement significantly, which means that it can have a direct and indirect effect on the improvement of student achievement in accounting in the form of partial mediation. Researchers recommend that student achievement in accounting will increase if the students' literacy of Computer Self-Efficacy and Internet Use can be mastered properly. Keywords: Computer Self Efficacy, Internet Usage, Study Interest, Learning Achievement, Accounting Students, Vocational High School